Do Institutional Ownership, Managerial Ownership, Independent Commissioners and Audit Committees Affect Earnings Persistence of Listed Manufacturing Companies Listed in Indonesia? - Zainal, Andri; Ritonga, Aslam Naufal Arrahman; Putra, Pasca Dwi; Harahap, Khairunnisa; Thohiri, Roza (Integrated Journal of Business and Economics (IJBE), 2024)
The issue of earnings persistence refers to the company's challenges in maintaining stable and consistent profits over time, especially in business. This research examines the influence of institutional ownership, managerial ownership, independent commissioners and audit committees on the persistence of profits of manufacturing companies listed on the Indonesia Stock Exchange (BEI). The sample in this research was 26 manufacturing companies from 2014 - 2022. A purposive sampling method was used to determine the quantitative research sample. The data analysis technique in this research uses descriptive statistical analysis and partial hypothesis testing. The analytical method in this research is by using multiple linear regression analysis. This research shows that institutional ownership, managerial ownership, independent commissioners, and audit committees significantly affect earnings persistence. The discussion of this research will be explained further in the following description.